The use of pseudorandom sweeps for vibroseis surveys. (10th November 2013) - Dean, T.
ABSTRACT Pseudorandom vibroseis sweeps have long been suggested as an alternative to standard linear sweeps due to their potential for having superior orthogonality, a lower likelihood for infrastructure damage, and increased low‐frequency content. In the past, they were also attractive as they have a better autocorrelation shape, although that is less important today. Their use has been limited but the increasing popularity of simultaneous acquisition techniques has rekindled interest as they offer the ability to reduce interference noise. A wide variety of methods for generating pseudorandom sweeps have been developed over the last 45 years. This paper gives an overview of the motivations for their use before classifying and describing the different sweep types. Finally, the sweeps will be compared in terms of their major attributes including their suitability for simultaneous surveys.